The Natural Moral Theory: An Idea: (Teori Moral Alamiah: Satu Gagasan) (Malay Literature, 2017)
For almost two centuries, Eastern scholars, Malays in particular, have employed Western theories in research. However, this has given rise to the realization that most Western theories are not compatible with the nature of Malay literature. From the end of the 20th century, some literature scholars, in Malaysia especially, began efforts to generate their own theories of literature and criticism. Their efforts have not been in vain. Over ten theories of literature and criticism have appeared on the literary scene. One of these is the Malay Methodology theory of Prof. Dato Dr. Hashim Awang (1998). This theory has been adopted by several students for their research theses, at the undergraduate right up to the doctoral level. However, there has been some criticism of the theory that has led to the formulation of a new theory, that of Natural Morality based on the fundamental principles of the Malay Methodology. This theory emphasizes the knowledge and experience available in literature, which is to be used as a model or an ideal to be imitated (mimesis) to enrich human knowledge. The knowledge contained in literary works is to be gleaned both directly and through inference/exegesis/interpretation of markers. Literature is the source of knowledge, and mimesis is a part of knowledge. Mimesis is not a one-way process but a circular one as readers can learn from reading literary works in order to achieve a harmonious life in the religious, societal and national sphere. In short, literary works contain knowledge of the material world and the hereafter, and are capable of moulding the mind and soul of a reader, apart from being beautiful.Keywords: experience, knowledge, ideal, mimesis, markers/symbols